Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

Role of macroalgal forests within Mediterranean shallow bays in blue carbon storage - Uxue Moreda; Inés Mazarrasa; Emma Cebrian; Joeri Kaal; Aurora M. Ricart; Eduard Serrano; Oscar Serrano (Science of The Total Environment, 2024)

Importance of life history traits for vulnerability to climate change: implications for macroalgal restoration - Sònia de Caralt; Jana Verdura; Jorge Santamaría; Alba Vergés; Emma Cebrian (Frontiers in Marine Science, 2023)
Fucalean algae are dominant canopy-forming species that create extensive and highly productive ecosystems in the intertidal and subtidal rocky shores of temperate seas. Regrettably, these marine forests are in decline due to various human drivers, with the Mediterranean Sea one of the most threatened areas. To design appropriate restoration strategies adapted to cope with the unavoidable change in future climate conditions, the response to climate change of the candidate species must be considered. It is important to assess how the specific life history traits of the foundational species may determine environmental requirements, and thus responses to future climate change. This knowledge will allow us to predict the potential winners and losers among the species potentially inhabiting the same areas in a future context of global climate change, providing important information to fine-tune future restoration interventions. The aim of this study was to evaluate the response of two canopy-forming species inhabiting similar upper subtidal zones but with different life history traits to a combination of anomalous high temperatures and increased UV radiation. One of the species ( Ericaria crinita ) was perennial, slightly exposed rocky shores and dwelling in areas where extreme temperatures can be frequent; while the other ( Ericaria mediterranea ) a semi-perennial species that dwells in wave-exposed zones, with seawater temperatures buffered by the high hydrodynamism. Our results show that the effects of temperature and radiation are species- (mediated by the species life history traits) and life-stage specific. High temperatures strongly affected the adults of both species, especially E. mediterranea . The germlings in addition to being very susceptible to high temperatures, were also vulnerable to UV radiation, exacerbating the impacts of temperature, especially on E. crinita recruits. Interestingly, vulnerability to climate-driven impacts was determined by the specific life history traits, with i) the species dwelling in open areas the most sensitive to warming and, ii) the perennial species the most vulnerable to UV radiation. Last, we discuss how these species-specific responses to climate-driven impacts may be key in terms of species that could foster the resistance and resilience of marine ecosystems to future climate impacts.

Distribution, health and threats to Mediterranean macroalgal forests: defining the baselines for their conservation and restoration - Jana Verdura; Lluc Rehues; Luisa Mangialajo; Simonetta Fraschetti; Zahira Belattmania; Silvia Bianchelli; Aurélie Blanfuné; Brahim Sabour; Antonia Chiarore; Roberto Danovaro; Erika Fabbrizzi; Sylvaine Giakoumi; et al. (Frontiers in Marine Science, 2023)
The worldwide decline of macroalgal forests is raising major concerns for the potentially negative consequences on biodiversity and ecosystem functions, pushing for the definition of specific conservation and restoration measures. Protecting and restoring these habitats requires detailed information on their distribution, ecological status, and drivers of decline. Here, we provide the most updated available information on the distribution of Mediterranean Cystoseira s.l. forests by conducting a comprehensive bibliographic survey of literature published from 2009 to 2021, complemented by unpublished data. We also provide insights into the ecological status of these forests and the stressors affecting them across the Mediterranean basin. Our results show that most Mediterranean coasts remain un(der)studied and that the available information is concentrated in spatially limited coastal areas, restricted to very few species. When the ecological status is reported, data is highly heterogeneous, making any comparisons problematic, what claims for the description and use of easy and standardized monitoring methods for comparative purposes. Drivers of decline of Cystoseira s.l. forest have been even less investigated and, therefore, still poorly characterized. Our results highlight that our current knowledge is still insufficient to implement effective conservation and restoration strategies at the basin scale but also regionally. We call for the urgent need for mapping and standardized monitoring of Cystoseira s.l. forests to obtain baseline information for future management strategies involving their conservation, the mitigation of the stressors threatening them and the restoration of the degraded forests.

Standardized protocol for reproductive phenology monitoring of fucalean algae of the genus Cystoseira s.l. with potential for restoration - Fabio Rindi; Alba Vergés; Irene Zuchegna; Silvia Bianchelli; Sònia de Caralt; Cristina Galobart; Jorge Santamaría; Francesco Martini; Margalida Monserrat; Sotiris Orfanidis; Cèlia Sitjà; Soultana Tsioli; et al. (Frontiers in Marine Science, 2023)
Active marine restoration is strongly encouraged to prevent the loss of the valuable habitats formed by Cystoseira sensu lato species, since they enhance biodiversity and preserve ecosystem functions and services. Current restoration interventions are mainly based on recruitment enhancement methods by deploying bags with fertile receptacles in situ or by outplanting juveniles grown ex situ under laboratory conditions. These methods allow the recovery of endangered species avoiding the depletion of the donor populations. In all cases, a priori knowledge of the reproductive phenology and recruitment periods of the species to be restored is essential, since the success of restoration techniques relies on collecting fertile branches and the obtention and survival of recruits. For their collection, identified donor populations characterized by dense Cystoseira s.l. cover should be studied. Specifically, monitoring the reproductive phenology of populations is crucial to detect the period of the year in which they develop mature reproductive structures and to understand how it might be linked to environmental conditions. Then, these general patterns on the reproductive phenology of Cystoseira s.l. species are essential to determine the most suitable time and conditions to plan for the most effective restoration action. Here, we provide a cost-effective and friendly protocol that can be easily and widely implemented for all Cystoseira s.l. species. We pose that this protocol provides a standardized and useful methodology to understand the environmental factors driving the optimal periods for sampling fertile branches across the Mediterranean Sea, and thus it can be an essential tool to plan future restoration actions.

A decision-support framework for the restoration of Cystoseira sensu lato forests - Christopher J. Smith; Jana Verdura; Nadia Papadopoulou; Simonetta Fraschetti; Emma Cebrian; Erika Fabbrizzi; Margalida Monserrat; Matilde Drake; Silvia Bianchelli; Roberto Danovaro; Dania Abdul Malak; Enric Ballesteros; et al. (Frontiers in Marine Science, 2023)
Macroalgal forests characterised by species of the genus Cystoseira sensu lato form important shallow coastal rocky habitats in the Mediterranean Sea. These forests support a high biodiversity and provide important ecosystem services and societal benefits. Currently these habitats are often in a poor condition in many areas, due to loss and degradation from both anthropogenic and climate stressors. Restoration has recently moved to the forefront of the United Nations and European Union agendas to reverse this trend, particularly in the last decade with the implementation of various international policies. However, this has been in the form of generic targets (e.g., restoration of 30% of degraded habitats by 2030) and has not been linked to specifically what habitat or species to restore, where and how. Initial targets have been missed, new targets are expected through the proposed EU Nature Restoration Law, but overall guidance is still lacking. There are few specific guides to marine habitat restoration limited to mostly seagrass, corals and shellfish. As a priority action for the recovery of coastal marine ecosystems a decision-support framework has been developed for the restoration of Mediterranean macroalgal forests, comprising a stepwise decision tree with additional descriptions of key elements to be considered for a restoration action. The decision tree includes steps concerning current and historical forest presence, site local condition assessment and choice of actions. Key considerations include restoration implementation (competence, society and support, finance and governance), success evaluation (at the target species and the ecosystem level) and long-term management. The framework builds on existing work on Cystoseira s.l. restoration, the work carried out in the EU AFRIMED project, but also on principles and guidelines in place for both generic and specific marine habitats. The work reported here has involved the expertise of scientists and information from stakeholders. Gaps were identified and recommendations were made, dealing with stressors, coordinating and networking stakeholders, integrating top down policy and bottom up initiatives, funding of restoration actions, establishing synergies between restoration, conservation and marine spatial planning and finally communication and publicity.

Addressing marine restoration success: evidence of species and functional diversity recovery in a ten-year restored macroalgal forest - Cristina Galobart; Enric Ballesteros; Raül Golo; Emma Cebrian (Frontiers in Marine Science, 2023)
Active restoration actions are becoming increasingly common for the recovery of degraded ecosystems. However, establishing when an ecosystem is fully restored is rarely achieved, since the recovery of entire communities needs long-term trajectories. The lack of evidence of success is even more severe in marine ecosystems, especially in the context of macroalgal forests, where beyond the vegetation structure and species diversity there is no approximation determining the recovery of the overall functionality. Trait-based ecology facilitates the link between species composition and ecosystem functions and processes. In this study, we used a trait-based approach to assess functional recovery ten years after the start of a restoration action in a marine macroalgal forest. Species and functional diversity were compared among the restored locality, a nearby locality where the expansion of the restoration is naturally occurring, a neighbouring non-restored locality (at a distance of a few meters), and the only two remaining localities dominated by the same structural macroalga that were used as reference (non-perturbed). Species diversity and composition of the restored locality were similar to those found in reference macroalgal forests, while the non-restored and expansion locality showed different species composition and lower species diversity. Functional richness was 4-fold higher in the restored locality than in the non-restored one, even surpassing one reference macroalgal locality. The restored locality showed a greater number of trait categories, especially traits related to higher structural complexity and longer life spans, indicating changes in ecosystem functions and processes. The restoration of a canopy-forming macroalga is the first step to achieving the recovery of an entire macroalgal forest (i.e., associated species and functional diversity). The application of traditional taxonomical indices plus functional parameters provides useful insights into the assessment of the success of restoration actions at the community level, emerging as a promising approach to be replicated and contrasted in other marine and terrestrial ecosystems.

Metabarcoding the eukaryotic community of a threatened, iconic Mediterranean habitat: Posidonia oceanica seagrass meadows - Xavier Turon; Jesús Zarcero; Adrià Antich; Owen Simon Wangensteen; Enric Ballesteros; Emma Cebrian; Candela Marco-Méndez; Teresa Alcoverro (Frontiers in Marine Science, 2023)
Against the accelerating pace of worldwide species extinction, reliable biodiversity assessments are critical, both as baselines and to track potential declines. DNA metabarcoding techniques allow for fast and comprehensive assessment of biodiversity in both terrestrial and marine habitats. However, these methods need to be adapted and standardised for each ecosystem in order to be effective. Seagrass meadows are among the most diverse marine habitats and are irreplaceable in terms of the ecosystem services they provide, yet metabarcoding has never been implemented for these systems. In this study, we developed and tested a protocol for metabarcoding the eukaryotic community of meadows of the iconic species, Posidonia oceanica L. (Delile). This seagrass is the main habitat-forming species in Mediterranean coastal waters and is known for its high diversity due to the structural complexity of its canopy and rhizome structures. This habitat is experiencing a range-wide retreat, and there is an urgent need for fast and efficient methods for its biomonitoring and detection of early changes. Our proposed method involves direct sampling of the community, collecting and processing the leaves and rhizome strata separately. To test the utility of the method in distinguishing between different meadow conditions, we sampled two distinct meadows that differ in their prevailing wind and surge conditions, and a nearby rocky reef for comparison. We then adapted a method and pipeline for COI metabarcoding using generalist primers that target the eukaryote diversity present. We detected a high diversity in the two meadows analysed (3,350 molecular operational taxonomic units, dominated by Metazoa and Archaeplastida) and a clear differentiation of the seagrass samples from those of the nearby rocky reefs. The leaves and rhizomes harboured clearly distinct assemblages, and differences were also detected between the two meadows sampled. This new tool has the potential to deliver big biodiversity data for seagrass habitats in a fast and efficient way, which is crucial for the implementation of protection and management measures for this key coastal habitat.

Capacity of countries to reduce biological invasions - Guillaume Latombe; Hanno Seebens; Bernd Lenzner; Franck Courchamp; Stefan Dullinger; Marina Golivets; Ingolf Kühn; Brian Leung; Núria Roura-Pascual; Emma Cebrian; Wayne Dawson; Christophe Diagne; et al. (Sustainability Science, 2023)
The extent and impacts of biological invasions on biodiversity are largely shaped by an array of socio-economic and environmental factors, which exhibit high variation among countries. Yet, a global analysis of how these factors vary across countries is currently lacking. Here, we investigate how five broad, country-specific socio-economic and environmental indices (Governance, Trade, Environmental Performance, Lifestyle and Education, Innovation) explain country-level (1) established alien species (EAS) richness of eight taxonomic groups, and (2) proactive or reactive capacity to prevent and manage biological invasions and their impacts. These indices underpin many aspects of the invasion process, including the introduction, establishment, spread and management of alien species. They are also general enough to enable a global comparison across countries, and are therefore essential for defining future scenarios for biological invasions. Models including Trade, Governance, Lifestyle and Education, or a combination of these, best explained EAS richness across taxonomic groups and national proactive or reactive capacity. Historical (1996 or averaged over 1996–2015) levels of Governance and Trade better explained both EAS richness and the capacity of countries to manage invasions than more recent (2015) levels, revealing a historical legacy with important implications for the future of biological invasions. Using Governance and Trade to define a two-dimensional socio-economic space in which the position of a country captures its capacity to address issues of biological invasions, we identified four main clusters of countries in 2015. Most countries had an increase in Trade over the past 25 years, but trajectories were more geographically heterogeneous for Governance. Declines in levels of Governance are concerning as they may be responsible for larger levels of invasions in the future. By identifying the factors influencing EAS richness and the regions most susceptible to changes in these factors, our results provide novel insights to integrate biological invasions into scenarios of biodiversity change to better inform decision-making for policy and the management of biological invasions.

The challenge of setting restoration targets for macroalgal forests under climate changes - Erika Fabbrizzi; Sylvaine Giakoumi; Francesco De Leo; Laura Tamburello; Antonia Chiarore; Alberto Colletti; Marianna Coppola; Marco Munari; Luigi Musco; Fabio Rindi; Lucia Rizzo; Beatrice Savinelli; et al. (Journal of Environmental Management, 2023)

Learning takes time: Biotic resistance by native herbivores increases through the invasion process - Jorge Santamaría; Raül Golo; Jana Verdura; Fiona Tomas; Enric Ballesteros; Teresa Alcoverro; Rohan Arthur; Emma Cebrian (Ecology Letters, 2022)
As invasive species spread, the ability of local communities to resist invasion depends on the strength of biotic interactions. Evolutionarily unused to the invader, native predators or herbivores may be initially wary of consuming newcomers, allowing them to proliferate. However, these relationships may be highly dynamic, and novel consumer–resource interactions could form as familiarity grows. Here, we explore the development of effective biotic resistance towards a highly invasive alga using multiple space‐for‐time approaches. We show that the principal native Mediterranean herbivore learns to consume the invader within less than a decade. At recently invaded sites, the herbivore actively avoided the alga, shifting to distinct preference and high consumptions at older sites. This rapid strengthening of the interaction contributed to the eventual collapse of the alga after an initial dominance. Therefore, our results stress the importance of conserving key native populations to allow communities to develop effective resistance mechanisms against invaders.

Marine heatwaves drive recurrent mass mortalities in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez‐Gras; Alba Medrano; Carlo Cerrano; Massimo Ponti; Robert Schlegel; Nathaniel Bensoussan; Eva Turicchia; Maria Sini; Vasilis Gerovasileiou; Nuria Teixido; Alice Mirasole; et al. (Global Change Biology, 2022)
Climate change is causing an increase in the frequency and intensity of marine heatwaves (MHWs) and mass mortality events (MMEs) of marine organisms are one of their main ecological impacts. Here, we show that during the 2015–2019 period, the Mediterranean Sea has experienced exceptional thermal conditions resulting in the onset of five consecutive years of widespread MMEs across the basin. These MMEs affected thousands of kilometers of coastline from the surface to 45 m, across a range of marine habitats and taxa (50 taxa across 8 phyla). Significant relationships were found between the incidence of MMEs and the heat exposure associated with MHWs observed both at the surface and across depths. Our findings reveal that the Mediterranean Sea is experiencing an acceleration of the ecological impacts of MHWs which poses an unprecedented threat to its ecosystems' health and functioning. Overall, we show that increasing the resolution of empirical observation is critical to enhancing our ability to more effectively understand and manage the consequences of climate change.

A Roadmap for the Restoration of Mediterranean Macroalgal Forests - Emma Cebrian; Laura Tamburello; Jana Verdura; Giuseppe Guarnieri; Alba Medrano; Cristina Linares; Bernat Hereu; Joaquim Garrabou; Carlo Cerrano; Cristina Galobart; Simonetta Fraschetti (Frontiers in Marine Science, 2021)
Canopy-forming macroalgae play a crucial role in coastal primary production and nutrient cycling, providing food, shelter, nurseries, and habitat for many vertebrate and invertebrate species. However, macroalgal forests are in decline in various places and natural recovery is almost impossible when populations become locally extinct. Hence, active restoration emerges as the most promising strategy to rebuild disappeared forests. In this regard, significant efforts have been made by several EU institutions to research new restoration tools for shallow and mesophotic reef habitats (e.g., MERCES EU project, AFRIMED, and ROCPOP-life) and effective techniques have subsequently been proposed to promote self-sustaining populations. Recent research indicates that macroalgal forest recovery requires a broad spectrum of measures, ranging from mitigating human impacts to restoring the most degraded populations and habitats, and that the viability of large restoration actions is compromised by ongoing human pressures (e.g., pollution, overgrazing, and climate change). We propose a roadmap for Mediterranean macroalgal restoration to assist researchers and stakeholders in decision-making, considering the most effective methods in terms of cost and cost-effectiveness, and taking background environmental conditions and potential threats into account. Last, the challenges currently faced by the restoration of rocky coastal ecosystems under changing climate conditions are also discussed.

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Effects of Natural and Anthropogenic Stressors on Fucalean Brown Seaweeds Across Different Spatial Scales in the Mediterranean Sea - Sotiris Orfanidis; Fabio Rindi; Emma Cebrian; Simonetta Fraschetti; Ina Nasto; Ergun Taskin; Silvia Bianchelli; Vasileios Papathanasiou; Maria Kosmidou; Annalisa Caragnano; Soultana Tsioli; Stefano Ratti; et al. (Frontiers in Marine Science, 2021)
Algal habitat-forming forests composed of fucalean brown seaweeds ( Cystoseira , Ericaria , and Gongolaria ) have severely declined along the Mediterranean coasts, endangering the maintenance of essential ecosystem services. Numerous factors determine the loss of these assemblages and operate at different spatial scales, which must be identified to plan conservation and restoration actions. To explore the critical stressors (natural and anthropogenic) that may cause habitat degradation, we investigated (a) the patterns of variability of fucalean forests in percentage cover (abundance) at three spatial scales (location, forest, transect) by visual estimates and or photographic sampling to identify relevant spatial scales of variation, (b) the correlation between semi-quantitative anthropogenic stressors, individually or cumulatively (MA-LUSI index), including natural stressors (confinement, sea urchin grazing), and percentage cover of functional groups (perennial, semi-perennial) at forest spatial scale. The results showed that impacts from mariculture and urbanization seem to be the main stressors affecting habitat-forming species. In particular, while mariculture, urbanization, and cumulative anthropogenic stress negatively correlated with the percentage cover of perennial fucalean species, the same stressors were positively correlated with the percentage cover of the semi-perennial Cystoseira compressa and C. compressa subsp. pustulata . Our results indicate that human impacts can determine spatial patterns in these fragmented and heterogeneous marine habitats, thus stressing the need of carefully considering scale-dependent ecological processes to support conservation and restoration.

The role of competition and herbivory in biotic resistance against invaders: a synergistic effect - Jorge Santamaría; Fiona Tomas; Enric Ballesteros; Juan M. Ruiz; Jaime Bernardeau‐Esteller; Jorge Terrados; Emma Cebrian (Ecology, 2021)
Invasive species pose a major threat to global diversity, and once they are well established their eradication typically becomes unfeasible. However, certain natural mechanisms can increase the resistance of native communities to invaders and can be used to guide effective management policies. Both competition and herbivory have been identified as potential biotic resistance mechanisms that can limit plant invasiveness, but it is still under debate to what extent they might be effective against well‐established invaders. Surprisingly, whereas biotic mechanisms are known to interact strongly, most studies to date have examined single biotic mechanisms separately, which likely influences our understanding of the strength and effectiveness of biotic resistance against invaders. Here we use long‐term field data, benthic assemblage sampling, and exclusion experiments to assess the effect of native assemblage complexity and herbivory on the invasion dynamics of a successful invasive species, the alga Caulerpa cylindracea . A higher complexity of the native algal assemblage limited C. cylindracea invasion, probably through competition by canopy‐forming and erect algae. Additionally, high herbivory pressure by the fish Sarpa salpa reduced C. cylindracea abundance by more than four times. However, long‐term data of the invasion reflects that biotic resistance strength can vary across the invasion process and it is only where high assemblage complexity is concomitant with high herbivory pressure, that the most significant limitation is observed (synergistic effect). Overall, the findings reported in this study highlight that neglecting the interactions between biotic mechanisms during invasive processes and restricting the studied time scales may lead to underestimations of the true capacity of native assemblages to develop resistance to invaders.

Herbivory on the Invasive Alga Caulerpa cylindracea: The Role of Omnivorous Fishes - Jorge Santamaría; Fiona Tomas; Enric Ballesteros; Emma Cebrian (Frontiers in Marine Science, 2021)
Herbivory has long been considered an important component of biotic resistance against macroalgae invasions in marine habitats. However, most of the studies on herbivory of invasive algae refer only to consumption by strictly herbivorous organisms, whereas consumption by omnivorous species has been largely ignored and rarely quantified. In this study, we assess whether the commonest omnivorous sparid species in the Mediterranean Sea are consuming the highly invasive alga, Caulerpa cylindracea , and determine both, its importance in their diet and their electivity toward it as a source of food. Our results confirm that three of the four fish species studied regularly consume C. cylindracea , but in most cases, the importance of C. cylindracea in the diet is low. Indeed, the low electivity values indicate that all species avoid feeding on the invasive alga and that it is probably consumed accidentally. However, despite animals and detritus being the main food for these sparid species, several individual specimens were found to have consumed high amounts of C. cylindracea . This suggests a potential role that these fish species, being really abundant in shallow rocky bottoms, may play in controlling, to some extent, the abundance of the invader.

Marine biomonitoring with eDNA: Can metabarcoding of water samples cut it as a tool for surveying benthic communities? - Adrià Antich; Cruz Palacín; Emma Cebrian; Raül Golo; Owen S. Wangensteen; Xavier Turon (Molecular Ecology, 2021)
In the marine realm, biomonitoring using environmental DNA (eDNA) of benthic communities requires destructive direct sampling or the setting‐up of settlement structures. Comparatively much less effort is required to sample the water column, which can be accessed remotely. In this study we assess the feasibility of obtaining information from the eukaryotic benthic communities by sampling the adjacent water layer. We studied two different rocky‐substrate benthic communities with a technique based on quadrat sampling. We also took replicate water samples at four distances (0, 0.5, 1.5, and 20 m) from the benthic habitat. Using broad range primers to amplify a ca. 313 bp fragment of the cytochrome oxidase subunit I gene, we obtained a total of 3,543 molecular operational taxonomic units (MOTUs). The structure obtained in the two environments was markedly different, with Metazoa, Archaeplastida and Stramenopiles being the most diverse groups in benthic samples, and Hacrobia, Metazoa and Alveolata in the water. Only 265 MOTUs (7.5%) were shared between benthos and water samples and, of these, 180 (5.1%) were identified as benthic taxa that left their DNA in the water. Most of them were found immediately adjacent to the benthos, and their number decreased as we moved apart from the benthic habitat. It was concluded that water eDNA, even in the close vicinity of the benthos, was a poor proxy for the analysis of benthic structure, and that direct sampling methods are required for monitoring these complex communities via metabarcoding.

Stressful Conditions Give Rise to a Novel and Cryptic Filamentous Form of Caulerpa cylindracea - Jorge Santamaría; Raül Golo; Emma Cebrian; María García; Alba Vergés (Frontiers in Marine Science, 2021)
Morphological plasticity can enable algae to adapt to environmental change and increase their invasibility when introduced into new habitats. Nevertheless, there is still a lack of knowledge on how such plasticity can affect the invasion process of an invasive species. In this context, the high plasticity in the genus Caulerpa is well documented. However, after an extremely hot summer, a previously unreported filamentous morphology of Caulerpa cylindracea was detected; indeed, this morphology could only be confirmed taxonomically after in-depth morphological characterization and molecular analysis with the genetic marker tuf A. We describe an ex situ culture experiment which showed that stressful conditions, such as high temperatures, can trigger this morphological change. Almost all of the thalli maintained at a constant extreme temperature of 29°C died, but after being returned to optimum temperature conditions, the filamentous morphology began to develop from the surviving microscopic tissue. In contrast, thalli at a control temperature of 21°C maintained the regular morphology throughout the experiment. When C. cylindracea develops this filamentous morphology, it may act as a cryptic invader because it is difficult to detect in the field. Furthermore, the filaments likely improve C. cylindracea ’s invasive capabilities with regard to resistance, persistence and dispersion and may have an important role in the re-colonization process, after a population disappears following a period of stressful conditions. Possibly, C. cylindracea ’s ability to respond plastically to stressful conditions might explain its remarkable success as an invasive species.

Habitat Features and Their Influence on the Restoration Potential of Marine Habitats in Europe - Trine Bekkby; Nadia Papadopoulou; Dario Fiorentino; Chris J. McOwen; Eli Rinde; Christoffer Boström; Marina Carreiro-Silva; Cristina Linares; Guri Sogn Andersen; Elizabeth Grace Tunka Bengil; Meri Bilan; Emma Cebrian; et al. (Frontiers in Marine Science, 2020)

Modeling Macroalgal Forest Distribution at Mediterranean Scale: Present Status, Drivers of Changes and Insights for Conservation and Management - Erika Fabbrizzi; Michele Scardi; Enric Ballesteros; Lisandro Benedetti-Cecchi; Emma Cebrian; Giulia Ceccherelli; Francesco De Leo; Alan Deidun; Giuseppe Guarnieri; Annalisa Falace; Silvia Fraissinet; Chiara Giommi; et al. (Frontiers in Marine Science, 2020)

Collaborative Database to Track Mass Mortality Events in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez-Gras; Jean-Baptiste Ledoux; Cristina Linares; Nathaniel Bensoussan; Paula López-Sendino; Hocein Bazairi; Free Espinosa; Mohamed Ramdani; Samir Grimes; Mouloud Benabdi; Jamila Ben Souissi; et al. (Frontiers in Marine Science, 2019)

Postglacial range expansion shaped the spatial genetic structure in a marine habitat‐forming species: Implications for conservation plans in the Eastern Adriatic Sea - Jean‐Baptiste Ledoux; Maša Frleta‐Valić; Silvija Kipson; Agostinho Antunes; Emma Cebrian; Cristina Linares; Pablo Sánchez; Raphael Leblois; Joaquim Garrabou (Journal of Biogeography, 2018)
Aim Understanding how historical and contemporary processes shaped and maintain spatial patterns of genetic diversity is a major goal for conservation biologists. Here, we characterized the pattern of neutral genetic diversity and we inferred underlying processes in the habitat‐forming octocoral Paramuricea clavata in the Adriatic Sea, a peculiar phylogeographic region of the Mediterranean Sea. Location Eastern coast of the Adriatic Sea. Methods We genotyped seven microsatellites in 454 individuals of P. clavata from 13 populations recolonized after the Last Glacial Maximum ( LGM ). We estimated the levels of contemporary connectivity and genetic drift and we reconstructed the demographic history of these populations. Results The pattern of spatial genetic structure resulted from the combination of hierarchical genetic clusters and isolation by distance ( IBD ). A significant decrease in genetic diversity and an increase of the frequencies of individual alleles likely due to allele surfing from the south to the north of the area were observed as expected after a postglacial sequential recolonization. Based on maximum likelihood analyses, the foundation of these populations was not linked to dramatic change in population size. Main conclusion Oceanographic barriers to gene flow combined to the restricted dispersal of P. clavata likely maintain the hierarchical structure and the IBD pattern. We suggest that the latitudinal genetic gradient results from a northward “serial founder events” recolonization. By integrating patterns and processes, we bridge the gap between the evolutionary and the conservation biology of P. clavata , providing management guidelines, which will benefit the associated coralligenous biodiversity.

Biodiversity influences invasion success of a facultative epiphytic seaweed in a marine forest - Emma Cebrian; Fiona Tomas; Paula López-Sendino; Montserrat Vilà; Enric Ballesteros (Biological Invasions, 2018)

Structure and biodiversity of coralligenous assemblages over broad spatial and temporal scales - Edgar Casas-Güell; Núria Teixidó; Joaquim Garrabou; Emma Cebrian (Marine Biology, 2015)

Rapid recovery from injuries in the temperate long-lived coral Cladocora caespitosa - Clara Casado; Diego K. Kersting; Emma Cebrian; Núria Teixidó; Joaquim Garrabou; Cristina Linares (Marine Biodiversity, 2015)

Impact of an invasive alga (Womersleyella setacea) on sponge assemblages: compromising the viability of future populations - Sonia de Caralt; Emma Cebrian (Biological Invasions, 2013)

Exploring the effects of invasive algae on the persistence of gorgonian populations - Emma Cebrian; Cristina Linares; Christian Marschal; Joaquim Garrabou (Biological Invasions, 2012)

Do native herbivores provide resistance to Mediterranean marine bioinvasions? A seaweed example - Emma Cebrian; Enric Ballesteros; Cristina Linares; Fiona Tomas (Biological Invasions, 2011)

Contrasting Effects of Heavy Metals on Sponge Cell Behavior - Emma Cebrian; María Jesús Uriz (Archives of Environmental Contamination and Toxicology, 2007)

Arsenic exposure and human papillomavirus response in non-melanoma skin cancer Mexican patients: a pilot study - J.Alberto Rosales-Castillo; LeonorC. Acosta-Saavedra; Rosantina Torres; Jess Ochoa-Fierro; VctorH. Borja-Aburto; Lizbeth Lopez-Carrillo; GonzaloG. Garcia-Vargas; GeorginaB. Gurrola; MarianoE. Cebrian; EmmaS Caldern-Aranda (International Archives of Occupational and Environmental Health, 2004)